Exploration of students' perceptions of science practicals as a bridge to meaningful learning - Sidawati, Asriyani Nurro; Susilowati, Ari; Astuti, Dina; Rahmayanti, Dinia Ika; Yulianti, Yuli; Musliman, Acep (JPBIO (Jurnal Pendidikan Biologi), 2026)
Twenty-first-century science education requires not only conceptual mastery but also the development of scientific process skills and critical thinking. Laboratory work plays a central role in achieving these goals; however, its effectiveness is often limited by “cookbook-style” procedures that fail to promote deep cognitive engagement. This study aimed to explore students’ perceptions of science practicums as indicators of Meaningful Learning (Pembelajaran Bermakna/PBM). Using a qualitative approach with an exploratory case study design, this research involved twelve purposively selected Grade VIII students. Data were collected through in-depth interviews, non-participant observation, and documentation, and were analyzed using thematic analysis. The findings indicate that students perceive meaningful learning as conceptual understanding that can be applied to everyday life rather than mere memorization. Science practicums were viewed as an effective means of achieving PBM, particularly due to the quality of teacher guidance, clear instructions, and opportunities for group collaboration. Although limited laboratory equipment and materials were identified as the main constraints, these limitations did not substantially hinder students’ conceptual understanding. The study concludes that strong pedagogical interactions can bridge hands-on and minds-on learning and support the implementation of competency-based curricula.